2022
DOI: 10.1002/cam4.5326
|View full text |Cite
|
Sign up to set email alerts
|

RUNX2 interacts with SCD1 and activates Wnt/β‐catenin signaling pathway to promote the progression of clear cell renal cell carcinoma

Abstract: Background: Previous studies have demonstrated that Runt-associated transcription factor 2 (RUNX2) serves as the main transcription factor for osteoblast differentiation and chondrocyte maturation. RUNX2 is related to a variety of tumors, particularly tumor invasion and metastasis, while the expression and molecular mechanisms of RUNX2 in clear cell renal cell carcinoma (ccRCC) keep to be determined. Stearyl CoA desaturase 1 (SCD1), an endoplasmic reticulum fatty acid desaturase, transfers saturated fatty acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Meanwhile, the dysregulation and alteration of RUNX2 expression or activity may result in arteriosclerosis, skeletal dysplasia (e.g., cleidocranial dysplasia) and tumorigenesis (4,(12)(13)(14). For instance, RUNX2 is involved in the progression of various tumor types, such as osteosarcoma, renal cell carcinoma, gastric cancer and breast cancer (15)(16)(17)(18)(19)(20). For instance, a recent study by our group reported the facilitating effect of RUNX2 during aggressiveness and chemoresistance of TNBC cells via activating MMP1, which was significantly associated with poor prognosis (21).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the dysregulation and alteration of RUNX2 expression or activity may result in arteriosclerosis, skeletal dysplasia (e.g., cleidocranial dysplasia) and tumorigenesis (4,(12)(13)(14). For instance, RUNX2 is involved in the progression of various tumor types, such as osteosarcoma, renal cell carcinoma, gastric cancer and breast cancer (15)(16)(17)(18)(19)(20). For instance, a recent study by our group reported the facilitating effect of RUNX2 during aggressiveness and chemoresistance of TNBC cells via activating MMP1, which was significantly associated with poor prognosis (21).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have also con rmed that CAV1 expression is closely related to ESCC, and it could be a powerful prognostic marker for patients with ESCC [67][68][69] . RUNX2 is related to a variety of tumors, particularly tumor invasion and metastasis [70] . It has been reported that RUNX2 was highly expressed in esophageal carcinoma tissues and cells, while knockdown of RUNX2 markedly suppressed tumor formation in vivo [71] .…”
Section: Discussionmentioning
confidence: 99%
“…In ccRCC, RUNX2 triggered cancer cell proliferation via SCD1-dependent Wnt/β-catenin pathway activation. RUNX2 downregulation inhibited cancer cell proliferation [ 11 ]. In another study of ccRCC, the biological function of RUNX2 was to increase focus formation, Ki67-positive staining, and tumor volume in a xenograft model.…”
Section: Runx2 and Cancer Proliferationmentioning
confidence: 99%
“…The role of RUNX2 in the clear cell subtype of RCC (ccRCC) cell migration was addressed. RUNX2 overexpression led to an increase in cell migration ability, and this elevated migration was partially reduced by the downregulation of SCD1 [ 11 ]. Activation of Zic2/Runx2/NOLC1 signaling promoted ccRCC cell migration and lung metastasis in vivo [ 12 ].…”
Section: Runx2 and Cancer Metastasismentioning
confidence: 99%